A dual-responsive colorimetric probe for the detection of Cu2+ and Ni2+ species in real water samples and human serum. Issue 23 (17th October 2019) - Yin, Guoxing; Yao, Jingfeng; Hong, Sai; Zhang, Yinuo; Xiao, Zhaohua; Yu, Ting; Li, Haitao; Yin, Peng
Abstract : The monitoring of heavy transition metals has increasingly attracted great attention because they pollute the environment and have unique physiological functions. Abstract : The monitoring of heavy transition metals has increasingly attracted great attention because they pollute the environment and have unique physiological functions. Chemosensors are useful tools for monitoring heavy transition metals due to their simple visualization, excellent sensitivity and high selectivity. Herein, we have developed a novel chemosensor for the detection of water-soluble Cu 2+ and Ni 2+ species with different mechanisms, and low detection limits of 2.1 nM for Cu 2+ and 1.2 nM for Ni 2+ were obtained. The colorimetric probe CPH has been applied to qualitative and quantitative detection of Cu 2+ and Ni 2+ species in real samples.